Towards high−resolution cardiac atlases: ventricular anatomy descriptors for a standardized reference frame - Schneider, P; Grau, V (Beijing‚ China, 2010)
Increased resolution in cardiac Magnetic Resonance Imaging (MRI) and growing interest in the effect of small structures in electro- physiology of the heart pose new challenges for cardiac atlases. In this paper we discuss the limitations of current atlas-building models when trying to incorporate cardiac small structure and argue for the need of developing a standard coordinate system for the heart that separates this from the macro-structure common to all individual hearts, in a way analogous to the stereotactic coordinate system from brain atlases. With this goal, we propose a set of methods to obtain two descriptors of the ventricular macro-structure that can be used to build a standardized reference frame: the central curve on the Left Ventricle cavity and the smoothed internal envelope of the Right Ventricle crest (i.e. the curve in the endocardial surface marking the junction between the right ventric- ular free wall and the septum).